Efficiently coupling water electrolysis with solar PV for green hydrogen production - Chi Zhang; Xinchang Yuan; Hao Fei; Min Ju; Hongsheng Wang; Yunze Zhang; Siyuan Wang; Ziyi Wang; Jia Lei; Guanzhen Chen; Yixiao Huang; Jian Wang (Energy Reviews)
Solar-driven water electrolysis has emerged as a prominent technology for the production of green hydrogen, facilitated by advancements in both water electrolyzers and solar cells. Nevertheless, the majority of integrated solar-to-hydrogen systems still struggle to exceed 20 ​% efficiency, particularly in large-scale applications. This limitation arises from suboptimal coupling methodologies and system-level inefficiencies that have rarely been analyzed. To address these challenges, this study investigates the fundamental principles of solar hydrogen production and examines key energy losses in photovoltaic-electrolyzer systems. Subsequently, it systematically discusses optimization strategies across three dimensions: (1) enhancing photovoltaic (PV) system output under variable irradiance, (2) tailoring electrocatalysts and electrolyzer architectures for high-performance operation, and (3) minimizing coupling losses through voltage-matching technologies and energy storage devices. Finally, we review existing large-scale solar hydrogen infrastructure and propose strategies to overcome barriers related to cost, durability, and scalability. By integrating material innovation with system engineering, this work offers insights to advance solar-powered electrolysis toward industrial applications.